Gest\~ao pública contemporânea: Do movimento gerencialista ao pós-NPM - Pedro Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The paper's main goal is to map trends in terms of management principles and directives, as well as transformations that permeate the public administration in the last decades. Grounded on the recent academic production, central issues are discussed in order to understand the changes in the public sector and to contribute to the theoretical debate and to future empirical investigations in an analytical framework of functions and, above all, innovative experiences. As a result, the literature converges to a perception of the principles and directives of post-NPM administration as a process of continuity or incrementalism rather than a rupture with the previous paradigm. However, when compared to the original assumptions of the Movement, regarding the dimensions of focus, inspirational source, strategic, fundamental beliefs, among others, the post-NPM differs categorically. In addition, the trends, as well as in the NPM, are present different forms, varying according to the context and institutional framework of each government. That is, institutions and history, endogeneously developed, matter for the understanding of the public administration framework. The most emblematic feature of the current public management is the prevalence of the governance, which in different formats can aggregate a significant part of the post-NPM principles and directives mapped in the literature. Finally, another central aspect of the debate is the incongruity of pure and complete overcoming of management paradigms, between NPM and traditional bureaucracy or between post-NPM and new public management. The literature suggests an incremental and disorderly process, independent of the country or the moment analyzed.
Keywords: H83; 330; reform; public administration; management; federal government